Body contouring system - Ali Tamimi Zhadekh (ХНУРЕ, 2022)
This method of external delivering ultrasound to the fat without depositing significant ultrasound energy in the skin would provide the benefits of ultrasound disruption of fat with greater safety. The 3D optical scanning system may be used to confirm the changes of body contours during this treatment.